Uniaxial dielectric media with hyperbolic dispersion relations - Mackay, Tom G. (2006)
Planewave propagation with hyperbolic/hyperboliclike characteristics in uniaxial dielectric media is investigated. The phase velocity is positive with respect to the time-averaged Poynting vector for both evanescent and nonevanescent propagation in nondissipative media, A conceptualization of a uniaxial medium, which exhibits hyperboliclike planewave characteristics as a homogenized composite medium, is presented. © 2005 Wiley Periodicals, Inc.